The experience of conducting collaborative and intensive pragmatic qualitative (CLIP-Q) research to support rapid public health and healthcare innovation - Horwood, Jeremy; Pithara, Christalla; Lorenc, Ava; Kesten, Joanna M.; Murphy, Mairead; Turner, Andrew; Farr, Michelle; Banks, Jon; Redwood, Sabi; Lambert, Helen; Donovan, Jenny L.; , NIHR ARC West Behavioural and Qualitative Science Team (Frontiers in Sociology, 2022)
A key challenge for qualitative methods in applied health research is the fast pace that can characterise the public health and health and care service landscape, where there is a need for research informed by immediate pragmatic questions and relevant findings are required quickly to inform decision-making. The Covid-19 pandemic accelerated the pace at which evidence was needed to inform urgent public health and healthcare decision-making. This required qualitative researchers to step up to the challenge of conducting research at speed whilst maintaining rigour and ensuring the findings are credible. This article illustrates how working with multidisciplinary, collaborative teams and the tailoring of qualitative methods to be more pragmatic and efficient can provide timely and credible results. Using time-limited case studies of applied qualitative health research drawn from the work of the Behavioural and Qualitative Science Team from the National Institute for Health and Care Research Applied Research Collaboration West (NIHR ARC West), we illustrate our collaborative and intensive pragmatic qualitative (CLIP-Q) approach. CLIP-Q involves i) collaboration at all stages of the design, conduct and implementation of projects and, where possible, co-production with people with lived experience, ii) an intensive team-based approach to data collection and analysis at pace and iii) pragmatic study design and efficient strategies at each stage of the research process. The case studies include projects conducted pre Covid-19 and during the first wave of the pandemic, where urgent evidence was required in weeks rather than months to inform rapid public health and healthcare decision making.